2019
DOI: 10.1007/s42413-019-00022-0
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being and the 2008 Recession in European Regions: The Moderating Role of Quality of Governance

Abstract: How can we explain why some regions experienced large decreases in subjective wellbeing during the 2008 recession, while in other regions, the changes were only very modest? Building on the literature on resilience in subjective well-being during periods of crisis, this article explores a related but undervalued factor that moderates the localized relationship between macroeconomic developments and life evaluation: regional quality of governance. We use individual-level data on life satisfaction and personal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Happiness scholars often emphasize that politics should expand human well‐being, and research on subjective well‐being has focused to a large extent on how political institutions and policies might influence happiness (e.g., Frey & Stutzer, ; Radcliff, ; Arampatzi et al, ). However, a relatively new strand of literature asserts that subjective well‐being also has a place as an independent variable in our political economy models (Di Tella & MacCulloch, ; Flavin & Keane, ; Healy, Kosec & Hyunjung Mo, ; Liberini et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Happiness scholars often emphasize that politics should expand human well‐being, and research on subjective well‐being has focused to a large extent on how political institutions and policies might influence happiness (e.g., Frey & Stutzer, ; Radcliff, ; Arampatzi et al, ). However, a relatively new strand of literature asserts that subjective well‐being also has a place as an independent variable in our political economy models (Di Tella & MacCulloch, ; Flavin & Keane, ; Healy, Kosec & Hyunjung Mo, ; Liberini et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Happiness scholars often emphasize that politics should expand human well-being, and research on subjective well-being has focused to a large extent on how political institutions and policies might influence happiness (e.g., Frey & Stutzer, 2000;Radcliff, 2001;Arampatzi et al, 2019). However, a relatively new strand of literature asserts that subjective well-being also has a place as an independent variable in our political economy models (Di Tella & MacCulloch, 2005;Flavin & Keane, 2012;Healy, Kosec & Hyunjung Mo, 2017;Liberini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Bartolini et al (2013) argue that if economic growth does not come with a reduction in (the quality of) social capital or relational goods, then happiness can well rise. Focusing specifically on the economic crisis, several studies have found that the negative impact of an economic crisis on subjective well-being can be alleviated by institutional and social trust (Helliwell et al 2014), social capital (Gudmundsdottir 2013), and the presence of unemployment support programmes and employment protection legislation (Morgan 2018), and good quality of governance (Arampatzi et al 2019). Many studies at the micro-level within nations have confirmed that people who earn a relatively high income tend to be happier than their less well earning fellow citizens.…”
Section: Later Researchmentioning
confidence: 99%